Biodiversity of Ants from Marathwada Region, Maharashtra, India: A Review of Ant Biodiversity in Marathwada Region, Maharashtra, India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Because of their widespread distribution, ants are the most important elements of the terrestrialecosystem and account for a larger portion of biomass. Ants are the most diverse group of social insectsand make up a significant portion of the terrestrial biosphere. These play the role of ecosystem engineers.They contribute significantly to the ecosystem by enhancing the soil and contributing in thedecomposition process, and because of their mutualistic interactions with both flora and fauna, they areregarded as reliable biological indicators. In this article, the biodiversity of ants in Maharashtra'sMarathwada area is reviewed.